Time effect of pile-soil interaction and its elastic-viscoplastic constitutive model (Rudarsko-geološko-naftni zbornik, 2018)
Pile-soil interaction is considered to be one of the most important problems in the study of the mechanical behaviour of pile foundation. In this paper, the lateral friction resistance and pile-soil relative displacement of bridge piles in deep soft soils are monitored for an extended period by using concrete strain gauges that are embedded in the test pile. Field test results show that both the pile lateral frictional resistance and pile-soil relative displacement increase along with time, while the pile-soil interaction demonstrates a time effect. Therefore, an elastic-viscoplastic constitutive model must be established to better simulate the time-dependent mechanical behaviour of the pile-soil contact. Based on the Goodman model, we developed an elastic-viscoplastic interface constitutive model of the pile-soil interface into the FRIC subrou- tine through ABAQUS software, which is one of the most commonly used finite element analysis softwares in the world, to simulate a well-recorded pile test in deep soft soils. The calculated pile lateral frictional resistance and pile-soil relative displacement are close to the measured values, and the ability of the interface model to describe the changes in the shear stress-strain of the pile-soil interface along with time is validated.